The music of Simon Holt - Charlton, David 1946- (Boydell Press, 2017)
British composer Simon Holt (b. 1958) has been a leading presence in contemporary music since the early 1980s and Kites. His output is diverse, comprising chamber music, concertos for diverse instruments, songs, piano music and opera. Holt is a composer who demands unusual commitment from his interpreters - the intricate sound-worlds he creates often contain complex, rich textures, offset by 'still centres' - for the purpose of making music which speaks with extraordinary power. Bringing together well-known writers with composers and performers, this volume gives a complete overview of Holt's creative work up to 2015 and Fool is hurt. It uses a variety of approaches to help readers, listeners and players to find ways into the pieces and to understand the influence of visual art and poetry on Holt's work. Colour illustrations, music examples, tables and sketch facsimiles offer a rounded impression of Holt's inspiration and thought to date. Also included are a wide-ranging conversation between Simon Holt and the artist Julia Bardsley, and a text by the conductor Thierry Fischer. The volume also offers the first detailed catalogue of Holt's compositions, drawn up together with the composer. It reveals that the last twenty years have seen no slowing-up in his rate of creative production, notwithstanding that the nature of his writing has changed during this time. - DAVID CHARLTON is Professor Emeritus of Music History, Royal Holloway, University of London.